Pediatrics Residents' Preparedness for Neonatal Resuscitation Assessed Using High-Fidelity Simulation - Cordero, Leandro (The Accreditation Council for Graduate Medical Education, 2013)
BACKGROUND: Pediatrics residents are expected to demonstrate preparedness for neonatal resuscitation, yet research has shown gaps in residents' readiness to perform this skill. OBJECTIVE: To evaluate procedural skills and team performance of pediatrics residents during neonatal resuscitation (NR) using a high-fidelity mannequin, and to assess residents' confidence in their NR skills before and after training. METHODS: Two teams of residents (all had completed NR program training) participated in 2 separate, 90-minute sessions (2 to 3 weeks apart) in an off-site delivery room during their neonatal intensive care rotation. Residents' confidence in assisting and leading NR was surveyed before each session. Teams participated in a scenario (adapted from the NR program), which required 5 skills (positive pressure ventilation, chest compressions, endotracheal intubation, umbilical vein catheterization, and epinephrine administration). Video recording was used for debriefing and scoring. Skills were scored for technique and timeliness, and team behaviors were scored for communication, management, and leadership. RESULTS: Twenty-six residents (11 teams) completed 2 paired sessions. Self-confidence scores increased between the 2 sessions but were not correlated with performance. Gaps in procedural skill performance were observed, and timeliness for most skills did not meet expectations. Significant improvement in team communication was noted. CONCLUSIONS: Important gaps in procedural skill performance, particularly timeliness, were detected by NR simulation training; residents' improvements in self-confidence did not reflect gains in actual performance. Their relative unpreparedness for NR (despite prior certification) highlights the need for deliberate practice and specific team training before and during neonatal intensive care delivery room rotations.